Boosting fast ignition heating through interaction between ultrahigh-contrast heating lasers and a cone-shaped target - Ryunosuke Takizawa; Alessio Morace; Yuki Abe; Yasunobu Arikawa; Baojun Zhu; Hiroki Morita; Zechen Lan; Jinyuan Dun; Takumi Tsuido; Yuga Karaki; Hiroki Matsubara; King Fai Farley Law; et al. (Physical Review Research)
In pursuing a carbon-neutral society, inertial fusion energy is a pivotal technology, offering a sustainable and virtually limitless energy source. Enhancing plasma heating efficiency is crucial for inertial fusion energy, following the ignition success using the laser-indirect-drive central-ignition approach at the U.S. National Ignition Facility. Fast ignition is a potentially high-efficiency approach among inertial confinement fusion methods. However, it remains significantly challenging due to the large divergence angle of relativistic electron beams (REBs) produced by high-intensity laser pulses. Here, we demonstrate the spontaneous collimation of REBs facilitated by an ultrahigh contrast of the heating laser in conjunction with a cone-shaped target. This collimation doubles the plasma heating efficiency compared to that achieved with the lower-contrast laser, as conducted with LFEX laser at Osaka University. This finding enables the use of a larger spot laser under ignition conditions, which is crucial for achieving the heating efficiency required for fusion ignition by reducing laser intensity and the mean kinetic energy of REBs. This collimation method significantly advances the field of inertial confinement fusion, elevating fast ignition to a practical level.